Multi-parametric assessment of left ventricular hypertrophy using late gadolinium enhancement, T1 mapping and strain-encoded cardiovascular magnetic resonance - Giusca, Sorin; Steen, Henning; Montenbruck, Moritz; Patel, Amit R.; Pieske, Burkert; Erley, Jennifer; Kelle, Sebastian; Korosoglou, Grigorios (Journal of cardiovascular magnetic resonance, 2021)
Methods:  314 patients (228 with hypertensive heart disease (HHD), 45 with hypertrophic cardiomyopathy (HCM), 41 with amyloidosis, 22 competitive athletes, and 33 healthy controls) were systematically analysed. LV ejection fraction (LVEF), LV mass index and interventricular septal (IVS) thickness, T1 mapping and atypical late gadolinium enhancement (LGE) were assessed. In addition, the percentage of LV myocardial segments with strain ≤ − 17% (%normal myocardium) was determined. - Results:  Patients with amyloidosis and HCM exhibited the highest IVS thickness (17.4 ± 3.3 mm and 17.4 ± 6 mm, respectively, p < 0.05 vs. all other groups), whereas patients with amyloidosis showed the highest LV mass index (95.1 ± 20.1 g/m2, p < 0.05 vs all others) and lower LVEF compared to controls (50.5 ± 9.8% vs 59.2 ± 5.5%, p < 0.05). Analysing subjects with mild to moderate hypertrophy (IVS 11-15 mm), %normal myocardium exhibited excellent and high precision, respectively for the differentiation between athletes vs. HCM (sensitivity and specificity = 100%, Area under the curve; AUC% normalmyocardium = 1.0, 95%CI = 0.85-1.0) and athletes vs. HHD (sensitivity = 83%, specificity = 75%, AUC%normalmyocardium = 0.85, 95%CI = 0.78-0.90). Combining %normal myocardial strain with atypical LGE provided high accuracy also for the differentiation of HHD vs. HCM (sensitivity = 82%, specificity = 100%, AUCc ombination = 0.92, 95%CI = 0.88-0.95) and HCM vs. amyloidosis (sensitivity = 83%, specificity = 100%, AUCc ombination = 0.83, 95%CI = 0.60-0.96). - Conclusion:  Fast-SENC derived myocardial strain is a valuable tool for differentiating between athletes vs. HCM and athletes vs. HHD. Combining strain and LGE data is useful for differentiating between HHD vs. HCM and HCM vs. cardiac amyloidosis.